Correlation Of Severity Of Malocclusion To The Abo Blood Group In Indian Subjects - S Dagdiya, Manish.; Nayak, Subash Chandra; Mendhe, Dr Prachi; Kumar Jha, Awanindra (Journal of Neonatal Surgery, 2025)
Background: Malocclusion represents irregularity in the teeth of affected subjects and is one of the major dental healthcare concerns seen globally. Malocclusion is being described as having multifactorial etiology. However, there has been comprehensive research on malocclusion, and existing data is limited on the correlation of malocclusion severity to ABO blood grouping. Aim: The present study aimed to assess the correlation of severity of malocclusion to the ABO blood group in Indian subjects using DAI (Dental Aesthetic Index). Methods: The study assessed 800 subjects aged 15-28 who reported to the Department of Orthodontics and Dentofacial Orthopedics within the defined study period. The subjects were divided into different groups based on their blood group type. Data gathered were statistically analyzed to assess any correlation between the severity of malocclusion to the ABO blood group. Results: The study results showed that there was a significant correlation in the severity of malocclusion to the ABO blood group with the highest incidence of malocclusion in blood group A followed by the O blood group, B blood group and the least incidence was seen in subjects with blood group AB with a p-value of <0.05. Conclusions: The present study concludes that rapid diagnosis, early intervention, and adequate treatment planning can help reverse malocclusion. This can be attained with periodic and regular dental visits during the child's developmental phase.